Orbital-angular-momentum fluorescence emission based on photon–electron interaction in a vortex field of an active optical fiber - Wu Yan; Wen Jianxiang; Tang Fengzai; Pang Fufei; Guo Hairun; Huang Sujuan; Wang Tingyun (Nanophotonics, 2022)
We develop a model of interaction between photons and electrons in an active vortex field, which can generate a fluorescence spectrum with the characteristics of orbital angular momentum (OAM). In an active optical fiber, our findings generalize the notion of photon–electron interaction and point to a new kind of OAM-mode broad-spectrum light source, which could be interpreted in two processes: one microscopically is the excitation of OAM-carrying photons based on the photon–electron interaction; the other macroscopically is the emission and transmission of a donut-shaped fluorescence in a vortex field with a spiral phase wavefront in a ring-core active fiber. Here we present a straightforward experimental method that the emission of broad-spectrum fluorescence with an OAM feature is actualized and validated in a ring-core erbium-doped fiber. The spectrum has a broad spectral width up to 50 nm. Furthermore, four wavelengths are extracted from the fluorescence spectrum and superimposed with their corresponding Gaussian beams, from which the spiral-shaped interferograms of OAM modes in a broad spectrum are identified with high purity. The application of the OAM-based fluorescence light source may range from classical to quantum information technologies, and enable high-capacity communication, high-sensitivity sensing, high-resolution fluorescence imaging, etc.